Hubungan Karakter Disiplin Dengan Minat Belajar Pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas IV SDN 13 Marga Mulya - Yonatan Yonatan; Eka Murdani; Mertika Mertika (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
The quality of Indonesia's education system is greatly influenced by how well the people in education apply discipline. Without high discipline, an educational institution will fall behind other nations that enforce strict discipline. This study aims to: 1) describe the discipline of fourth grade students of SDN 13 Marga Mulya, 2) describe the interest in learning Pancasila education in fourth grade students of SDN 13 Marga Mulya, and 3) describe the relationship between discipline and interest in learning Pancasila education in fourth grade students of SDN 13 Marga Mulya. This study used a quantitative correlational research design. The population was the fourth grade students of SDN 13 Marga Mulya. The sample used was a total sampling of all fourth grade students of SDN 13 Marga Mulya, consisting of 30 students. The prerequisite test used was a normality test. The results of the normality test using SPSS showed a significance value of 0.070>0.05, indicating a normal distribution of the data. The results of the study indicate a significant correlation between discipline and students' interest in learning. The correlation coefficient was 0.41, indicating a fairly strong correlation. Discipline plays a significant role in influencing interest in learning Pancasila Education, contributing 17% of the correlation. The remaining 83% is influenced by other factors. The implications of this study suggest the need for efforts to improve students' discipline to positively impact their interest in learning.